دور أخلاقيات العمل في تعزيز سلوك المواطنة التنظيمية في الجامعات الحكومية دراسة تحليلية لآراء رؤساء الأقسام في الجامعات الحكومية في إقليم كوردستان العراق - فتاح, ئافا عمر; فرج, كاوە محمد (Sulaimani Journal for Humanities, 2018)
The research aims to identifying the effect of the dimensions of work ethic in the behavior of organizational citizenship in the public universities in the Kurdistan Region. After reviewing previous studies on work ethic and organizational citizenship behaviors, theoretical concepts were written and research questions were constructed. Where a questionnaire was designed to collect data. A questionnaire was distributed to the respondents of the heads of departments in the public universities in the Kurdistan Region of Iraq (329). A number of tests were carried out before and after the distribution of the questionnaire to verify its validity, stability and reliability, and to ascertain its validity in measuring the variables of study such as virtual truth, comprehensiveness, consistency, content validity, neutrality and internal consistency. Several statistical methods were used to analyze the data and answer the hypotheses. The results showed statistically significant effect on the variable of work ethic in the organizational citizenship variable. Based on the results of the research, a number of recommendations and suggestions were presented, as well as a proposal to encourage leaders to participate in volunteer work, help others and disseminate work ethics that contribute to improving the image of the university.
Keywords: Work ethics; organizational citizenship; special grades; governmentuniversities; Kurdistan Region